Effect of nonsurgical periodontal therapy on C-reactive protein and iron indices in hemodialysis patients - Sheethel Menon Vrinda; Arun Sadasivan; Elizabeth Koshi; Beena Unnikrishnan; Nikhil Das Chandradas; Indhuja Raveendran Saraswathi (Wolters Kluwer Medknow Publications, 2021)
Background and Aim: The aim of the study was to evaluate the effect of nonsurgical periodontal therapy on clinical, renal, and hematological parameters at baseline and 3 months postoperatively on chronic kidney disease (CKD) patients undergoing hemodialysis. This comparative interventional study was conducted among CKD patients undergoing hemodialysis. Materials and Methods: This study included chronic periodontitis (CP) patients divided into three groups Group I: CKD patients undergoing hemodialysis for less than a year; Group II: CKD patients undergoing hemodialysis for more than a year; and Group III: systemically healthy CP patients. Clinical parameters (bleeding on probing [BOP], probing pocket depth (PPD), and clinical attachment level [CAL]) were recorded at baseline (T0), 1 month (T1), and 3 months after scaling and root planing (SRP) (T2). C-reactive protein (CRP) and transferrin saturation (TSAT) were observed at T0 and at T2. Paired t-test and Chi-square test were applied to find the statistical significance (P < 0.05 was considered statistically significant at 95% confidence interval) between the T0 and T2 time within the groups. Results: Clinical parameters such as PPD and CAL decreased with statistical significance in Group III alone, whereas BOP decreased with statistical significance in all the three groups. The study showed statistically significant reduction of CRP (in Group I and Group III) and TSAT increased with statistical significance in all the three groups after SRP. Conclusion: This suggests that SRP can bring an improvement in the systemic markers in CP patients under hemodialysis. However, we need a longitudinal study with a larger sample size to confirm the results.